THE ROLE OF NUSANTARA INSIGHTS FOR GENERATION Z THROUGH LOCAL WISDOM - Salamah, Devita Putri; Utaminingsih, Esty Setyo; Ummah, Siti Siska Knikmahtul (Universitas Indraprasta PGRI, 2024)
The rapid development of technology threatens the preservation of Nusantara insight values among Generation Z, as these values are traditionally imparted through local wisdom. The weakening of these cultural values risks diminishing a sense of nationalism and identity in modern Indonesian youth. This research examines the role of Nusantara insight in fostering these values among Generation Z. The study employed a literature review method, analyzing articles from 2016 to 2023 relevant to Nusantara insights and their transmission through local wisdom. Data collection involved using academic databases such as Google Scholar, Academia Edu, and Research Gate. The collected data were analyzed qualitatively to derive conclusions about the significance of these values. The results showed that Nusantara's insights are crucial in strengthening national identity, encouraging unity amidst diversity, and guiding Generation Z in globalization. It was also found that reinforcing Nusantara values through education and community engagement is critical for cultural preservation. Additionally, the integration of technology and local wisdom was found to be a practical approach to maintaining cultural values. In conclusion, Nusantara's insights, supported by local wisdom, are essential in shaping a nationalistic and culturally aware Generation Z.